Strategy for Human Capital Development in The Entrepreneurial Environment in The Digital Era - Rostini; Arimbawa, I Gede Arya Pering; Goeliling, Ardhie; Vianti, Nela Nur; A Rahman, Fatmawati (PT. Maju Malaqbi Makkarana, 2025)
In the digital era, entrepreneurship has undergone significant transformation, particularly in human capital management. This study explores strategies for human capital development within digital entrepreneurial environments, focusing on digital skills training, collaborative learning, and flexible work arrangements. Using a qualitative approach, data were collected through semi-structured interviews, focus group discussions (FGDs), and document analysis. The findings indicate that entrepreneurs who adopt digital-based human capital development strategies experience improvements in workforce skills, innovation, and business productivity. However, challenges such as limited resources, resistance to change, and digital literacy gaps remain significant barriers, particularly for small and medium enterprises (SMEs). This study highlights the role of leadership and digital platforms as solutions to overcome these obstacles. The findings provide valuable insights for business practitioners and policymakers in designing more effective and sustainable human capital development strategies in the digital age.